Antecedents of sustainable supply chain initiatives: Empirical evidence from the S&P 500. (10th March 2020) - Sebastianelli, Rose; Tamimi, Nabil
Abstract: Prior research on sustainable supply chain management (SSCM) has almost exclusively focused on environmental aspects (GSCM—green supply chain management) and the study of its external drivers and consequences. Framing our study within the "strategy‐conduct‐performance" paradigm, we consider the focal firm's role in the implementation of sustainable supply chain initiatives, social as well as environmental. We use data on the S&P 500 Index retrieved from Bloomberg, including variables for two relevant focal firm strategies: (a) reducing the environmental footprint of the supply chain and (b) reducing social risks in the supply chain (SRSS). Hierarchical logit modeling is carried out to examine the sequential impact of governance board characteristics and the focal firm's adoption of related internal policies and practices on the likelihood of implementing these initiatives along the supply chain. Controlling for industry, firm size, and resources, we find that board structure and diversity influence the implementation of sustainable supply chain initiatives by increasing organizational commitment to environmentally friendly and socially responsible policies and practices. Consequently, empirical evidence exists for the importance of strategic factors, namely a proactive corporate stance on sustainability associated with governance board characteristics, as antecedents of sustainable (environmental and social) supply chain initiatives.